Pelatihan Pengolahan Data Menggunakan Spreadsheet untuk Meningkatkan Kinerja Administrasi - Candra Naya; Eko Budiarto; Suryadi; Unggul Prima Dhani (VINICHO MEDIA PUBLISINDO, 2026)
Effective community administration requires accurate, well-structured, and easily accessible data management. However, based on observations conducted in Graha Asri Housing Complex RT 001 RW 012, Simpangan Village, North Cikarang, administrative data management is still performed manually or semi-digitally, resulting in delays in report preparation, potential recording errors, and low administrative efficiency and transparency. In addition, community members have limited skills in using spreadsheet applications such as Microsoft Excel and Google Sheets. This community service program aims to improve the ability of neighborhood administrators and community members to manage administrative data using spreadsheet applications. The program employs a participatory approach consisting of socialization, hands-on training, technology implementation, mentoring, evaluation, and sustainability activities. The training materials include basic spreadsheet features, data processing, automated report generation, and data visualization using tables and charts. The expected outcomes include improved digital literacy, the availability of spreadsheet-based administrative templates, increased efficiency in report preparation, and the establishment of a more effective, transparent, and sustainable community administration system through the utilization of digital technology.